2019
DOI: 10.1029/2018wr024666
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of Gas Flow in Rough‐Walled Microfracture at In Situ Conditions

Abstract: The development of the unconventional gas and CO2 sequestration is moving to deep formations. Because of the small flow pathways in the matrix, the Knudsen number might be high even though the gas is dense. In fact, due to the relatively high pressure at in situ conditions, gas flow in microfractures usually manifests a strong slip and nonideal gas effects. Therefore, understanding the coupling mechanism of these two on gas flow in rough‐walled microfractures is required to accurately model subsurface flow beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…While many studies of flow through rough fractures have adopted no-slip boundary conditions at the solid–fluid interface, this assumption is not always justified in situations of practical interest such as non-wetting fluid flow (Lee, Yo & Lee 2013) or rarefied gas flow (Wang, Tang & Jing 2019). In the slip regime, characterised by a Knudsen number (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies of flow through rough fractures have adopted no-slip boundary conditions at the solid–fluid interface, this assumption is not always justified in situations of practical interest such as non-wetting fluid flow (Lee, Yo & Lee 2013) or rarefied gas flow (Wang, Tang & Jing 2019). In the slip regime, characterised by a Knudsen number (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluidics, introduced as an analogue to microfluidics, is defined as the study of fluids flowing within a characteristic length scale down to below 100 nm. Motivations to control fluid flow under such a highly confined condition arise from its tremendous implications in chemical engineering and nanotechnology, including nanofluidic energy conversion, ultrafiltration and separation, , and next-generation seawater desalination. , The main difference of nanofluidics from macro- and microfluidics lies in the fact that the interactions between a fluid and solid walls cannot be neglected because of a large surface-to-volume ratio. Surface forces, especially a friction force at a water–solid interface, dominate over volume forces at the nanoscale, leading to various unique transport phenomena. It is reported that for a flow dimension larger than 1–2 nm, a bulk phase exists and the continuum theory is still valid. However, the flow properties near a solid surface will be different from that of the bulk phase because of the impact of surface forces. This flow type is usually defined as a quasi-continuum state, indicating a bulk phase flow in the middle of a flow region and a unique boundary flow near a solid surface …”
Section: Introductionmentioning
confidence: 99%
“…8 The K values of coal reservoirs are mainly composed of 0.01-5 mD in China, which is lowered by 1-2 magnitudes than overseas, for example, the Powder River Basin in North America (>10 mD) and the Surat Basin in Austria (10-30 mD). 8,9,[19][20][21] The methane adsorbability of coal reservoirs tends to increase with increasing P o and decreasing T em . 8,9,[19][20][21] The methane adsorbability of coal reservoirs tends to increase with increasing P o and decreasing T em .…”
Section: Introductionmentioning
confidence: 99%
“…10,18 The research showed that in situ stress had obviously affected coal K, and the latter exponentially declined with the increasing of the former. 8,9,[19][20][21] The methane adsorbability of coal reservoirs tends to increase with increasing P o and decreasing T em . 22 By changing the confining pressure of pore fluid, the in situ stress regime can directly control P o and influence the gas-bearing conditions of the coal reservoir.…”
Section: Introductionmentioning
confidence: 99%